Swarm Intelligence Based Optimization : Second International Conference, ICSIBO 2016, Mulhouse, France, June 13-14, 2016, Revised Selected Papers /: Second International Conference, ICSIBO 2016, Mulhouse, France, June 13-14, 2016, Revised Selected Papers. (2016) - Unknown
No abstract available